Kinetics of drying inorganic spheres: Simultaneous modeling of moisture and temperature during the constant and falling rate periods. Issue 10 (27th July 2018) - Siles, J. A.; Martín, M. A.; Molina, E.; Martín, A.
ABSTRACT: The kinetics of the dehydration of four sizes of spherical inorganic materials was studied experimentally with warm air using a fixed-bed dryer at laboratory scale. Following the evaluation of the effect of bed thickness, air mass rate, and air temperature on drying kinetics, a kinetic model consisting of two equations was proposed. The main novelty of this study resides in the possibility of utilizing a new model for simultaneous heat and mass transfer in an efficient manner for practical applications and appropriate system optimization, especially during the falling rate period.